BATAK ETHNICITY IN T-SHIRT DESIGN IN NORTH SUMATERA - Kartono, Gamal; Zulkifli, Zulkifli; Lubis, Sulaiman (Universitas Negeri Medan, 2018)
AbstractT-shirt screen printing industry in Medan has not been able to design t-shirt products (t-shirts) that are typically based on local arts and culture, especially Batak, and have not been able to manage (manage) their business properly. On the other hand, the demands of consumers are the existence of products in the form of T-shirts (t-shirts) with nuances of local arts. To find a solution, the team has discussed it with the two partners. The method offered is in the form of transfer of knowledge and skills through intensive assistance, which is formulated in the form of education, training, demonstration, direct practice, and mentoring. In line with this, management is carried out, including marketing and branding, so that partner products get a good image and high selling value. In general, the results and benefits obtained by partners are: 1) an increase in partner knowledge about local arts-based design, which is unique as a local identity, 2) an increase in the ability to develop design and production of T-shirts by partners, and 3) increased production from T-shirt products based on Batak arts are expected to increase partner sales turnover.Keywords: Batak ethnicity, Design, T-shirt.